New Discoveries at Karatepe. A Complete Text of the Phoenician Royal Inscription from Cilicia - Obermann, J.
Duplicate or Parallel ? — Site and Disposition — Text — Commentary: Identity of the King, General Outline, Accomplishments in Particular, Citadel, Finale — Translation — Summary: Historical Situation, Significance of the Inscription — Addendum.